Compliance with IAS/IFRS and its Determinants: A Meta-Analysis - Khaled Samaha; Hichem Khlif; Khaled Dahawy (STIE Malangkucecwara, 2016)
The objective of this paper is to meta-analyze a set of 1? empirical papers dealing with the determinants of the degree of compliance with IASXIPRS standards. We consider firm size (proxy for agency theory), profitability [proxy for signaling theory), leverage (proxy for agency and signaling theories), auditor (proxy signaling theory), internationality (proxy for capital need theory), and ownership diffusion (proxy for agency theory). Our results provide evidence that firm size, auditor type, multi nationality, proﬁtability and ownership dispersion have a positive effect on IASXIFRS compliance. Compliance with IAS/IFRS in emerging markets is suongly associated vnth firm size, auditor type, leverage, profitability and ownership dispersion. Given the low disclosure envnonment, weak investors’ protection and capital external need prevailing in these contexts; these factors are likely to enhance corporate reporting policy. -Managers comply seriously with LAS/IFRS in developing countries to reduce agency costs, signal a higher financial statements’ credibility and get more easily external finance from financial institutions. Compliance with IASXIPRS in developed countries is associated with corporate size, audit firm size and muiti-nationality. In addition, investor protection level also moderates the association between corporate characteristics and compliance IAS/IFRS. For instance, in low investor protection settings, corporate size and profitability are more associated with LAS/IFRS compliance, while audit firm size, leverage and multi-nationa.lity increase the degree of compliance with IAS/IPRS in countries characterized by high protection level. The ﬁnding:-: emphasize the need to explicitly consider the legal and institutional setting when one analyzes the effect of corporate characteristics on IASXIFRS compliance.